2021
DOI: 10.3233/nre-201601
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric training effects for patients with post-stroke hemiparesis on strength and speed gait: A randomized controlled trial

Abstract: BACKGROUND: In hemiparetic patients, the skeletal muscle is mainly affected with a combination of abnormalities (denervation, remodeling, spasticity, and eventually muscular atrophy). OBJECTIVE: This study examined the role of eccentric exercise in strengthening muscles of the lower extremity and ultimately improving autonomy in patients with post-stroke hemiparesis during gait. METHODS: Thirty-seven patients hemiparetic adults were recruited, randomized into a control group (n = 19) and an intervention group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The justification where this movement improves the lower limb muscle strength leading to better static postural stability can be seen through its form, where it puts the quadriceps in eccentric contraction. According to a randomized controlled trial on hemiparesis patients, eccentric contraction of the quadriceps promotes lower limb strength based on one repetition maximum and gait performance based on six-minute-walk-test ( 67 ), although six-minute-walk-test incorporated with cognitive behavioral-based therapy has promising outcomes in pain ( 68 ). Besides, it was reported that eccentric muscle contractions were more effective for improving neuromuscular activation, strength, and walking speed than concentric contractions ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…The justification where this movement improves the lower limb muscle strength leading to better static postural stability can be seen through its form, where it puts the quadriceps in eccentric contraction. According to a randomized controlled trial on hemiparesis patients, eccentric contraction of the quadriceps promotes lower limb strength based on one repetition maximum and gait performance based on six-minute-walk-test ( 67 ), although six-minute-walk-test incorporated with cognitive behavioral-based therapy has promising outcomes in pain ( 68 ). Besides, it was reported that eccentric muscle contractions were more effective for improving neuromuscular activation, strength, and walking speed than concentric contractions ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of researchers have published work that describes the necessity of strength for mobility. For example, others have, reported relationships between strength improvement and gait speed [17][18][19][20], walking endurance [15,16,20], and balance and functional capability [21], but there is mixed evidence regarding recovery of function as a result of strength training. For example, Dorsch et al [50] conducted a systematic review of results from progressive resistance training; they reported a large effect size regarding strength improvement, but notably, there was no definitive effect at the level of activity.…”
Section: Strength Is a Necessary Pre-requisite But Not Sufficient To Restore Normal Gait After Stroke If Gait Dyscoordination Is Presentmentioning
confidence: 99%
“…For example, Dorsch et al [50] conducted a systematic review of results from progressive resistance training; they reported a large effect size regarding strength improvement, but notably, there was no definitive effect at the level of activity. Further, many studies have added importantly to knowledge in the field regarding possible gait training interventions but did not report recovery to normal for gait coordination, function, and life role participation (e.g., [15][16][17][18][19][20][21]51]). This situation begs the question, "What is the missing critical ingredient(s) in gait training interventions which would be sufficient to consistently produce functional and quality of life changes?".…”
Section: Strength Is a Necessary Pre-requisite But Not Sufficient To Restore Normal Gait After Stroke If Gait Dyscoordination Is Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of eccentric exercise in most studies ranged from medium- to high-intensity training, whereas the intensity was typically ≥50% of the maximal eccentric strength, derived from the multiple repetition maximum of eccentric exercise or related to maximal concentric strength (>60% of concentric 1RM—one-repetition maximum) [ 19 , 21 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. For instance, Johnson et al [ 19 ] found significant improvements after eccentric training program with intensity ranging from 30% to 50% of the maximal eccentric strength in functional tasks such as 30 s chair raise, timed up and go test, and maximal eccentric strength in the community of dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%